High-strength steel sheet, steel strip, producing method of high-strength steel sheet, producing method of steel strip and member

By controlling heating and annealing processes to manage Mn distribution and microstructure, the method addresses variations in mechanical properties of high-strength steel plates, achieving consistent yield ratio and dimensional accuracy for automobile parts.

JP2025002164AActive Publication Date: 2025-01-09JFE STEEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023102130
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-22
Publication Date
2025-01-09
Estimated Expiration
2043-06-22

AI Technical Summary

Technical Problem

Conventional methods for producing high-strength steel plates with a tensile strength of 980 MPa or more face challenges in maintaining consistent mechanical properties within a coil, leading to variations in yield ratio (YR) and dimensional accuracy, which affects the quality and productivity of automobile parts.

Method used

A manufacturing method that controls slab heating conditions, temperature, and annealing processes to manage Mn distribution and microstructure, ensuring a specific composition and microstructure of the steel, including controlled cooling and reheating steps to achieve a TS of 980 MPa or more, El of 10% or more, and YR of 50% to 85% with minimal variation.

Benefits of technology

The method produces high-strength steel plates with stable mechanical properties, enabling high dimensional accuracy and reduced variations, suitable for automobile parts, particularly in frame structure and reinforcement components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002164000001
    Figure 2025002164000001
  • Figure 2025002164000002
    Figure 2025002164000002
  • Figure 2025002164000003
    Figure 2025002164000003
Patent Text Reader

Abstract

To provide a high-strength steel sheet excellent in material stability to be a problem in a steel sheet of TS of 980 MPa or more, EL of 10% or more, YR of 50% or more and 85% or less, and 980 MPa class which is produced by a method simpler than the conventional technology, a steel strip, and a method for producing a high-strength steel sheet, a method for manufacturing a steel strip, and a member.SOLUTION: A high-strength steel sheet that has a specific component composition and structure, and is characterized by a ratio of 1.05 or more of an amount of Mn contained in tempered martensite to the amount of Mn contained in the steel sheet. However, the amount of Mn contained in tempered martensite is mass%. (Equation 1) Mn / (C+Si)≥1.2, C, Si, and Mn in Equation 1 all represent mass% of each element.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-strength steel sheet, a steel strip, a manufacturing method for a high-strength steel sheet, a manufacturing method for a steel strip, and a member. In particular, the present invention relates to a high-strength steel sheet, which has a TS of 980 MPa or more and an El of 10% or more, is suitable for use as a member in industrial fields such as automotive and electrical equipment formed by cold pressing, can be manufactured into parts with high dimensional accuracy, and has excellent material stability with little variation in YR, and is suitable for use as a member in industrial fields such as automotive and electrical equipment formed by cold pressing. [Background technology]

[0002] In recent years, there has been an increasing need to reduce the weight of automobile bodies in order to improve fuel efficiency from the standpoint of protecting the global environment. This has led to a demand for the application of high-strength steel sheets to automobile parts.

[0003] Conventionally, 780MPa and 980MPa grade steel sheets have been manufactured using DP steel with a dual-phase structure of ferrite and martensite, but DP steel in principle requires annealing at a two-phase temperature range.In particular, with 980MPa grade steel sheets, slight temperature changes in the two-phase temperature range cause abrupt changes in the ferrite and martensite fractions, which can lead to strength variations even within the same coil. In addition, high-strength steel sheets used in automotive reinforcement and frame structural parts are required to be able to manufacture parts with high dimensional accuracy. In order to manufacture parts with high dimensional accuracy, it is important to control the yield ratio of the steel sheet (YR = yield strength YS / tensile strength TS) within a certain range. By controlling the yield ratio (YR) of the steel sheet within a certain range, it is possible to suppress springback after steel sheet forming and increase the dimensional accuracy during forming. Furthermore, by increasing the yield ratio (YR) of the steel sheet, it is possible to increase the impact absorption energy of the part during a collision. However, if there is variation in mechanical properties within the same coil, there will be a difference in the amount of springback during part forming, which will lead to dimensional errors in the final formed part, and the productivity of the final product will be poor. Therefore, various studies are being conducted to manufacture steel sheets with less variation in mechanical properties within the same coil.

[0004] For example, Patent Document 1 specifies the area ratios of ferrite, bainitic ferrite, and martensite, the volume ratio and average crystal grain size of retained austenite, and further specifies that the average Mn content (mass %) in the retained austenite is at least 1.2 times the Mn content (mass %) in the steel, and that at least 60% of the total retained austenite is at least 2.1 times the C content (mass %) in the steel, thereby disclosing a technology for realizing a high-strength steel plate that has a tensile strength (TS) of 780 MPa or more, is excellent in not only ductility but also stretch flangeability, and also has excellent material stability.

[0005] Furthermore, Patent Document 2 discloses a technology for realizing a high-strength steel sheet having a tensile strength of 980 MPa or more, an elongation of 13% or more, and reduced variation in stretch flangeability, by specifying the area ratio of tempered martensite having a hardness of 330 Hv or more and 450 Hv or less, specifying the grain size of the remaining ferrite, and further specifying the upper limit / lower limit ratio of the Mn concentration in the cross section of the steel sheet in the thickness direction. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 021193 [Patent Document 2] JP 2010-65307 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the technology described in Patent Document 1 requires a process in which the cold-rolled steel sheet is heated to a temperature of 820°C or more and 950°C or less, cooled to the Ms point or less, and then heated again to a temperature of 740°C or more and 840°C or less, and then cooled, which is likely to result in high energy costs.

[0008] In addition, while the technique described in Patent Document 2 reduces the variation in stretch flangeability for steel sheets of 980 MPa or more, it does not take into consideration the variation in YR that is likely to be a problem for 980 MPa-class steel sheets.

[0009] Therefore, the present invention aims to provide a high-strength steel sheet, a steel strip, a manufacturing method for a high-strength steel sheet, a manufacturing method for a steel strip, and a member that have a TS of 980 MPa or more, an El of 10% or more, and a YR of 50% to 85%, and that are excellent in the material stability that is a problem with 980 MPa-class steel sheets, by a manufacturing method simpler than those of the prior art. The above-mentioned steel sheets refer to hot-rolled steel sheets, cold-rolled steel sheets, and plated steel sheets such as GA and GI, and the above-mentioned steel strips refer to steel strips (also called coils) made of the above-mentioned steel sheets.

[0010] YR is calculated using the following formula: YR = YS / TS x 100 (%) In the present invention, "capable of manufacturing parts with high dimensional accuracy (high dimensional accuracy during forming)" means that YR is 50% or more and 85% or less, and "excellent material stability" means that the variation in YR in the width direction of the steel plate is 10% or less. [Means for solving the problem]

[0011] In order to solve the above problems, the inventors have conducted extensive research into the chemical composition and microstructure of steel sheets, and have found that it is possible to control the Mn distribution in the steel and the steel sheet microstructure by controlling the slab heating conditions and the temperature from hot rolling to coiling, and by changing the amount of heat the steel sheet receives during annealing, and that it is possible to obtain a steel with high strength, a specified YR, and excellent material stability by controlling the subsequent cooling stop temperature and holding temperature. The present invention has been made based on the above findings, and the gist of the present invention is as follows. [1] In weight percent: C: 0.020% or more and 0.200% or less, Si: 0.01% or more and 2.00% or less, Mn: 2.50% or more and 5.00% or less, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, N: 0.0100% or less and O: 0.0100% or less, C, Si, and Mn satisfy the following formula 1, The balance is composed of Fe and unavoidable impurities, The microstructure of the steel plate is The total area ratio of ferrite and bainitic ferrite is 30% or more and 70% or less, The area ratio of tempered martensite is 10% or more and 60% or less. The area ratio of fresh martensite is 5% or more and 35% or less. The remainder is at least one of retained austenite and pearlite, with an area ratio of 0% to 20%. A high-strength steel plate, characterized in that the ratio of the amount of Mn contained in tempered martensite to the amount of Mn contained in the steel plate is 1.05 or more. However, the amount of Mn contained in the tempered martensite is expressed in mass %. (Formula 1)Mn / (C+Si)≧1.2 In formula 1, C, Si, and Mn each represent the mass percentage of each element. [2] Furthermore, the composition, by mass%, is Ti: 0.500% or less, Nb: 0.500% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less Co: 1.00% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, Bi: 0.200% or less, REM: 0.0100% or less, The high-strength steel plate according to [1], characterized in that it contains at least one or more elements selected from the following: [3] The high-strength steel plate according to [1] or [2], characterized in that the ratio of the amount of C contained in the fresh martensite to the amount of C contained in the steel plate is 1.50 or more. However, the C content in fresh martensite is expressed in mass percent. [4] The high-strength steel sheet according to any one of [1] to [3], characterized in that the steel sheet surface has a plating layer. [5] The high-strength steel plate according to [4], wherein the plating layer is an alloyed plating layer. [6] A steel strip comprising the high-strength steel plate according to any one of [1] to [3]. [7] A steel strip comprising the high strength steel plate according to [4] or [5]. [8] A method for producing a high strength steel plate according to any one of [1] to [3], A hot rolling process in which a steel material having the composition according to [1] or [2] is heated, hot rolling is performed at a finish rolling end temperature of 800°C or more, and then coiling is performed at a coiling temperature of 700°C or less; After the hot rolling process, A heating process in which the temperature is raised to a heating temperature T0 ° C. that is equal to or higher than Ac1 ° C. and satisfies formula 2, and then annealed at an annealing temperature T1 ° C. that satisfies formula 3, and the cooling start temperature is set to T1 ° C., and the average cooling rate is set to 5.0 ° C. / s or more from T1 ° C. to 400 ° C.; Next, the cooling is performed to a cooling stop temperature Tsq ° C., which is 150 ° C. to 370 ° C., and the temperature is increased to a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and then the holding temperature Toa ° C. is a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and the holding time is toa seconds. The time t from Ac1°C during the heating process to the heating temperature T0°C through the heating end temperature T1°C h The heat input parameter Q defined by the formula 4 based on the annealing time t seconds at the annealing temperature T1 ° C. and the annealing temperature T1 ° C. is 3200 or more and 4800 (° C. × min) or less, A manufacturing method of high strength steel plate, characterized in that in the reheating step, the holding temperature Toa °C, the holding time toa seconds, and the heat input parameter Q satisfy Equation 5. (Formula 2)T1 <T0 (Formula 3)720 <T1<Ac3+100 (Formula 4)Q=[{(Ac1+T1) / 2}×t h / 60] + T1×t / 60 (Equation 5) Q / 10≦Toa(logtoa) [9] A method for producing a steel strip according to the above [6], A hot rolling process in which a steel material having the composition according to [1] or [2] is heated, hot rolling is performed at a finish rolling end temperature of 800°C or more, and then coiling is performed at a coiling temperature of 700°C or less; After the hot rolling process, A heating process in which the temperature is raised to a heating temperature T0 ° C. that is equal to or higher than Ac1 ° C. and satisfies formula 2, and then annealed at an annealing temperature T1 ° C. that satisfies formula 3, and the cooling start temperature is set to T1 ° C., and the average cooling rate is set to 5.0 ° C. / s or more from T1 ° C. to 400 ° C.; Next, the cooling is performed to a cooling stop temperature Tsq ° C., which is 150 ° C. to 370 ° C., and the temperature is increased to a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and then the holding temperature Toa ° C. is a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and the holding time is toa seconds. The time t from Ac1°C during the heating process to the heating temperature T0°C through the heating end temperature T1°C h The heat input parameter Q defined by the formula 4 based on the annealing time t seconds at the annealing temperature T1 ° C. and the annealing temperature T1 ° C. is 3200 or more and 4800 (° C. × min) or less, A method for producing a steel strip, characterized in that in the reheating step, the holding temperature Toa°C, the holding time toa seconds, and the heat input parameter Q satisfy Equation 5. (Formula 2)T1 <T0 (Formula 3)720 <T1<Ac3+100 (Formula 4)Q=[{(Ac1+T1) / 2}×t h / 60] + T1×t / 60 (Equation 5) Q / 10≦Toa(logtoa)

[10] A method for producing a high strength steel plate according to [8], characterized in that cold rolling is performed after the hot rolling step and before the heating step.

[11] The method for producing a high-strength steel sheet according to [8] or

[10] , characterized in that after the reheating step, a plating treatment is carried out to form a plating layer on the steel sheet surface.

[12] The method for producing a high-strength steel plate according to

[11] , characterized in that the plating treatment is an alloying plating treatment to form an alloying plating layer.

[13] A method for producing a steel strip as described in [9], characterized in that cold rolling is performed after the hot rolling step and before the heating step.

[14] A method for producing a steel strip according to [9] or

[13] , characterized in that after the reheating step, a plating treatment is carried out to form a plating layer on the steel sheet surface.

[15] The method for manufacturing a steel strip according to

[14] , characterized in that the plating treatment is an alloying plating treatment to form an alloying plating layer.

[16] A member, characterized by using the high-strength steel plate according to any one of [1] to [5]. Effect of the Invention

[0012] According to the present invention, it is possible to obtain high-strength steel plates, steel strips and members having excellent material stability with TS of 980 MPa or more, El of 10% or more, YR of 50% to 85%, and little variation in YR. Therefore, the present invention is very useful in industrial fields such as automobiles and electrical equipment, and is particularly useful for reducing the weight of automobile body frame parts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. Note that "%" representing the content of each component element means "% by mass" unless otherwise specified. (1) The reasons for limiting the chemical compositions of the high strength steel plate (steel plate) and steel strip in the present invention to the above ranges will be explained.

[0014] C: 0.020% or more and 0.200% or less C is an element that affects the fraction and strength of tempered martensite, bainite, and fresh martensite. If the C content is less than 0.020%, the fraction of fresh martensite and tempered martensite decreases, making it difficult to obtain the desired TS. For this reason, the C content is set to 0.020% or more. It is preferably set to 0.022% or more, and more preferably set to 0.024% or more. On the other hand, if the C content exceeds 0.200%, the annealing temperature dependency of the strength of the martensite phase becomes too high, and the material stability is impaired. For this reason, the C content is set to 0.200% or less. It is preferably set to 0.180% or less. It is more preferably set to 0.160% or less.

[0015] Si: 0.01% or more and 2.00% or less Si is an element that contributes to solid solution strengthening and improves the strength of steel sheet. If the Si content is less than 0.01%, this effect is poor, so the Si content is set to 0.01% or more. It is preferably 0.02% or more, and more preferably 0.04% or more. On the other hand, since Si is an element that suppresses the formation of cementite, if the Si content exceeds 2.00%, C that has not precipitated as cementite bonds with elements that form carbides, such as Nb and Ti, and unrecrystallized ferrite is easily formed, especially during annealing, resulting in poor material stability. Therefore, the Si content is set to 2.00% or less. It is preferably set to 1.50% or less. More preferably, it is set to 1.00% or less.

[0016] Mn: 2.50% or more and 5.00% or less Mn is an element that affects the area ratio of tempered martensite and fresh martensite by improving hardenability. If the Mn content is less than 2.50%, the fraction of soft phases such as ferrite increases significantly with a slight decrease in annealing temperature, and the desired area ratio of tempered martensite and fresh martensite cannot be stably obtained, resulting in loss of material stability. For this reason, the Mn content is set to 2.50% or more. It is preferably set to 2.70% or more, more preferably set to 2.90% or more, and even more preferably set to 3.00% or more. On the other hand, if the Mn content exceeds 5.00%, the area ratio of ferrite decreases and ductility decreases. Therefore, the Mn content is set to 5.00% or less. It is preferably set to 4.50% or less. It is more preferably set to 4.00% or less. It is even more preferably set to 3.90% or less.

[0017] P:0.100% or less P may have an adverse effect on workability by segregating at grain boundaries and causing embrittlement, so its amount must be 0.100% or less. Therefore, the P content is set to 0.100% or less. It is preferably set to 0.080% or less. It is more preferably set to 0.050% or less. There is no particular lower limit, but since P is a solid solution strengthening element and can increase the strength of the steel sheet, it is preferably set to 0.001% or more.

[0018] S: 0.0200% or less S segregates at grain boundaries to embrittle steel during hot working, and may also adversely affect workability by forming sulfides, so its amount must be 0.0200% or less. Therefore, the S content is set to 0.0200% or less, preferably 0.0180% or less, and more preferably 0.0100% or less. There is no particular lower limit, but due to production technology constraints, it is preferable to set it to 0.0001% or more.

[0019] Al: 0.100% or less Al acts as a deoxidizer and is an effective element for reducing inclusions in steel, and is preferably contained in the deoxidization process. However, a large content of more than 0.100% increases the risk of steel slab cracking during continuous casting, reducing manufacturability. Therefore, the Al content is set to 0.100% or less. Preferably, it is set to 0.080% or less. More preferably, it is set to 0.070% or less. There is no particular lower limit for the Al content, but it is preferably set to 0.001% or more. More preferably, it is set to 0.005% or more.

[0020] N: 0.0100% or less N has a detrimental effect on material stability by forming coarse nitrides, and when the N content exceeds 0.0100%, a large amount of coarse nitrides is formed, resulting in significant deterioration of material stability. The smaller the amount, the better, so the N content is set to 0.0100% or less. It is preferably 0.0090% or less. It is more preferably 0.0080% or less. There is no particular lower limit, but it is preferably 0.0001% or more due to constraints on production technology.

[0021] O: 0.0100% or less O exists as an oxide and reduces the ultimate deformability of the steel sheet, which reduces the material stability. Therefore, the O content must be 0.0100% or less, and is preferably 0.0050% or less. There is no particular lower limit for the O content, but due to production technology constraints, the O content is preferably 0.0001% or more.

[0022] (Formula 1)Mn / (C+Si)≧1.2 In the formula 1, C, Si, and Mn each represent the mass percentage of the element contained in the steel. In addition to the above-mentioned composition, if the amount of Mn is small relative to the amounts of C and Si, the area ratio of the tempered martensite or fresh martensite formed will be small, while the strength of the tempered martensite or fresh martensite will be high, resulting in localized areas of high strength and areas of low strength, resulting in poor material stability. Therefore, it is necessary to satisfy formula 1. The right side of formula 1 is preferably 1.4. More preferably, the right side of formula 1 is 1.5. The upper limit is preferably Mn / (C+Si)<8.0.

[0023] In addition to the above components, the alloy may contain one or more selected from, by mass%, Ti: 0.500% or less, Nb: 0.500% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 1.00% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, Bi: 0.200% or less, and REM: 0.0100% or less.

[0024] Ti: 0.500% or less Ti contributes to precipitation strengthening, and further refines the prior austenite grain size and the accompanying tempered martensite and bainite, so it is effective in improving steel strength. However, if Ti is contained in an amount exceeding 0.500%, Ti may remain in an undissolved state during heating of the steel material before hot rolling, increasing the number of coarse precipitates and decreasing ductility. Therefore, when Ti is contained, the Ti content is set to 0.500% or less. Preferably, it is set to 0.100% or less. More preferably, it is set to 0.070% or less.

[0025] Nb: 0.500% or less Nb is an element that improves the strength of steel sheet by precipitation strengthening through the formation of fine precipitates. On the other hand, if the Nb content exceeds 0.500%, precipitates such as Nb carbides and nitrides become coarse, making it difficult to uniformly control the precipitates in the steel sheet, resulting in poor material stability. Therefore, when Nb is contained, the Nb content is set to 0.500% or less, preferably 0.100% or less, and more preferably 0.070% or less.

[0026] V:0.200% or less V contributes to precipitation strengthening, and further refines the prior austenite grain size and the accompanying tempered martensite and bainite, so it is effective in improving the strength of the steel. There is no particular lower limit, but in order to obtain the above effect, it is preferable to set the V content to 0.001% or more. However, if the V content exceeds 0.200%, V may remain in an undissolved state during heating of the steel material before hot rolling, increasing the amount of coarse precipitates and decreasing ductility. Therefore, when V is contained, the V content is set to 0.200% or less. Preferably, it is set to 0.180% or less.

[0027] Ta: 0.10% or less Ta, like Ti, produces alloy carbides and alloy carbonitrides to contribute to high strength, and also partially dissolves in Nb carbides and Nb carbonitrides to produce composite precipitates such as (Nb, Ta)(C, N). This significantly suppresses the coarsening of precipitates and stabilizes the contribution of precipitation strengthening to strength, so Ta can be included as necessary. There is no particular lower limit, but in order to obtain the above effect, it is preferable to make it 0.01% or more. However, even if Ta is included in excess, the precipitate stabilization effect is saturated and the alloy cost increases. Therefore, when Ta is included, the Ta content is 0.10% or less. It is preferably 0.08% or less. More preferably, it is 0.07% or less.

[0028] W: 0.10% or less W can be added as necessary to improve the hardenability of steel and to further improve the strength of steel by refining tempered martensite and bainite. The lower limit is not particularly limited, but in order to obtain the above effects, it is preferable to set it to 0.01% or more. However, if it is added in excess of 0.10%, the amount of coarse precipitates such as WN and WS remaining in an undissolved state during slab heating in hot rolling may increase, resulting in a decrease in ductility. Therefore, when W is added, the W content is set to 0.10% or less. It is preferably set to 0.08% or less. It is more preferably set to 0.05% or less.

[0029] B: 0.0100% or less B is an element that can improve hardenability by segregating at austenite grain boundaries, and can form a structure mainly composed of tempered martensite and bainite, thereby improving the strength of the steel sheet, and can be contained as necessary. Although the lower limit is not particularly limited, in order to obtain the above effect, it is preferable to set the content to 0.0003% or more. However, if it is contained in excess of 0.0100%, coarse precipitates are formed and ductility is reduced. Therefore, when B is contained, the B content is set to 0.0100 or less. It is preferably set to 0.0090% or less. It is more preferably set to 0.0080% or less. It is even more preferably set to 0.0070% or less.

[0030] Cr:1.00% or less Cr has the effect of improving the balance between strength and ductility, so it can be contained as necessary. The lower limit is not particularly limited, but in order to obtain the above effect, it is preferable to make it 0.01% or more. However, if it is contained in excess of 1.00%, the area ratio of fresh martensite becomes excessive, and the dimensional accuracy and ductility during forming are reduced. Therefore, when Cr is contained, the Cr content is 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.

[0031] Mo: 1.00% or less Mo has the effect of improving the balance between strength and ductility, so it can be contained as necessary. The lower limit is not particularly limited, but in order to obtain the above effect, it is preferable to make it 0.01% or more. However, if it is contained in excess of 1.00%, the area ratio of fresh martensite becomes excessive, and the dimensional accuracy and ductility during forming are reduced. Therefore, when Mo is contained, the Mo content is 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.

[0032] Co: 1.00% or less Co is an element effective in improving hardenability and is effective in strengthening steel, so it can be contained as necessary. There is no particular lower limit, but in order to obtain the above effects, it is preferable to make it 0.01% or more. However, if it is contained in an amount exceeding 1.00%, the area ratio of fresh martensite becomes excessively large, and the dimensional accuracy and ductility during forming decrease. Therefore, when Co is contained, the Co content is 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.

[0033] Ni: 1.00% or less Ni increases the strength of steel by solid solution strengthening, so it can be contained as necessary. There is no particular lower limit, but in order to obtain the above effect, it is preferable to make it 0.01% or more. However, if it is contained in excess of 1.00%, the area ratio of fresh martensite becomes excessive, and the dimensional accuracy and ductility during forming decrease. Therefore, when Ni is contained, the Ni content is 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.

[0034] Cu:1.00% or less Cu is an effective element for strengthening steel, so it can be contained as necessary. There is no particular lower limit, but in order to obtain the above effect, it is preferable to make it 0.01% or more. However, if it is contained in excess of 1.00%, the area ratio of tempered martensite, bainite, and fresh martensite becomes excessive, and the dimensional accuracy and ductility during forming decrease. Therefore, when Cu is contained, the Cu content is 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.

[0035] Sn: 0.200% or less, Sb: 0.200% or less Sn and Sb can be contained as necessary to suppress decarburization in a region of about several tens of μm in the surface layer of the steel sheet caused by nitriding or oxidation of the steel sheet surface, prevent the area ratio of tempered martensite on the steel sheet surface from decreasing, and ensure strength and material stability. Although there is no particular lower limit, in order to obtain the above effects, it is preferable that the content of these elements is 0.001% or more. However, for any of these elements, if they are contained in excess of 0.200%, the ductility may decrease due to embrittlement of the steel sheet. Therefore, when Sn and Sb are contained, the content of Sn and Sb is 0.200% or less. Preferably, it is 0.100% or less. More preferably, it is 0.050% or less.

[0036] Ca: 0.0100% or less, Mg: 0.0100% or less Ca and Mg are elements that make the shape of sulfides spheroidal. Although there is no particular lower limit, it is preferable that these contents are 0.0010% or more. However, excessive contents exceeding 0.0100% each may cause an increase in inclusions, cause surface and internal defects, and cause a decrease in ductility. Therefore, when Ca and Mg are contained, the contents of Ca and Mg are each 0.0100% or less. Preferably, they are 0.0090% or less. More preferably, they are 0.0080% or less.

[0037] Zr: 0.100% or less, Te: 0.100% or less Zr and Te can be contained as necessary to improve the hardenability of steel, generate fine carbides containing Zr, and improve the strength of steel by refining tempered martensite and bainite. Although there is no particular lower limit, it is preferable that the content of these elements is 0.001% or more. However, excessive content exceeding 0.100% may cause an increase in inclusions, cause surface and internal defects, and reduce ductility. Therefore, when Zr and Te are contained, the content of Zr and Te is 0.100% or less, respectively. Preferably, it is 0.080% or less. More preferably, it is 0.050% or less.

[0038] Hf: 0.10% or less Hf is an element that affects the distribution state of oxides. Although there is no particular lower limit, the content is preferably 0.001% or more. However, excessive addition of more than 0.10% increases coarse precipitates and inclusions, impairing the material stability of the steel sheet. Therefore, when Hf is contained, the Hf content is set to 0.10% or less, preferably 0.08% or less, and more preferably 0.05% or less.

[0039] Bi:0.200% or less If the Bi content is 0.200% or less, the amount of coarse precipitates and inclusions will not increase, and the material stability of the steel sheet will not be impaired. Therefore, when Bi is contained, the Bi content is set to 0.200% or less. It is preferably set to 0.150% or less. It is more preferably set to 0.100% or less. Although there is no particular lower limit, it is preferable that the content of these elements is set to 0.001% or more.

[0040] REM: 0.0100% or less REM is an element that makes the shape of sulfides spheroidal. Although there is no particular lower limit, the content of these elements is preferably 0.0010% or more. However, excessive content exceeding 0.0100% may cause an increase in inclusions, cause surface and internal defects, and cause a decrease in ductility. Therefore, the REM content is set to 0.0100% or less, preferably 0.0090% or less, and more preferably 0.0080% or less.

[0041] In addition, when the contents of the above-mentioned Ti, Nb, V, Ta, W, B, Cr, Mo, Co, Ni, Cu, Sn, Sb, Ca, Mg, Zr, Te, Hf, Bi and REM are less than the preferable lower limit values, the effects of the present invention are not impaired, and therefore these elements are included as unavoidable impurities.

[0042] (2) Next, the microstructure of high-strength steel plate (steel plate) will be explained.

[0043] Total area ratio of ferrite and bainitic ferrite: 30% to 70% Ferrite and bainitic ferrite contribute to the ductility of the steel sheet. If the total area ratio of ferrite and bainitic ferrite is less than 30%, the ductility will be less than 10%, so the sum of the area ratios of ferrite and bainitic ferrite must be at least 30% or more. It is preferably 32% or more. On the other hand, if the sum of the area ratios of ferrite and bainitic ferrite exceeds 70%, the steel structure will be dominated by relatively soft ferrite and bainitic ferrite, so the TS will be less than 980 MPa. Therefore, the sum of the area ratios of bainite and tempered martensite must be 70% or less. It is preferably 68% or less.

[0044] Area ratio of tempered martensite: 10% to 60% Tempered martensite contributes to the strength of the steel sheet. Also, including tempered martensite in the steel sheet structure is effective in maintaining high strength. When the area ratio of tempered martensite is less than 10%, the TS is less than 980 MPa. Therefore, the area ratio of tempered martensite must be at least 10% or more. It is preferably 12% or more. On the other hand, if the area ratio of tempered martensite exceeds 60%, the YR increases and the dimensional accuracy during forming decreases, so the area ratio of tempered martensite must be 60% or less. It is preferably 58% or less.

[0045] Area ratio of fresh martensite: 5% to 35% Fresh martensite is a very hard phase, and by dispersing fresh martensite in the structure, it is possible to obtain steel with excellent dimensional accuracy during forming. In order to fully obtain this effect, the area ratio of fresh martensite must be 5% or more. On the other hand, if the area ratio of fresh martensite exceeds 35%, ductility decreases, so the area ratio of fresh martensite must be 35% or less. It is preferably 6% or more and less than 32%. In the present invention, even if a residual structure such as ferrite, bainitic ferrite, retained austenite other than tempered martensite and fresh martensite, and pearlite is contained, the effect of the present invention is not impaired. When a residual structure is present, the residual structure includes at least one of retained austenite and pearlite, and specifically, the area ratio of at least one of retained austenite and pearlite is set to 0% or more and 20% or less. The area ratio of the residual structure is preferably 15% or less. More preferably, it is 10% or less. Further preferably, it is 5% or less.

[0046] The ratio of the amount of Mn contained in the tempered martensite to the amount of Mn contained in the steel sheet is 1.05 or more (however, the amount of Mn contained in the tempered martensite is expressed in mass%). Determining the ratio of the amount of Mn contained in the tempered martensite to the amount of Mn contained in the steel sheet is one of the important constituent items in the present invention. By controlling the amount of Mn distributed in austenite during annealing, the transformation to bainite, which has a large TS variation with respect to the holding temperature, is suppressed, and as a result, the YR is stabilized, a specified YR can be obtained, and a steel sheet with excellent material stability can be obtained. Since most of the regions that were austenite during annealing become tempered martensite in the final structure, in order to fully obtain such effects, the ratio of the amount of Mn contained in the tempered martensite to the amount of Mn contained in the steel sheet needs to be 1.05 or more. It is preferably 1.07 or more. It is more preferably 1.10 or more.

[0047] The ratio of the amount of C contained in the fresh martensite to the amount of C contained in the steel sheet is 1.50 or more (however, the amount of C contained in the fresh martensite is expressed in mass%) (preferred condition) The holding in the reheating process promotes C enrichment in the untransformed austenite remaining in the steel sheet. Since the strength of martensite is determined by the C content, determining the ratio of the C content in the fresh martensite to the C content in the steel sheet components is effective in making the TS 980 MPa or more. In addition, since the C enrichment in the untransformed austenite remaining in the steel sheet is promoted, the transformation to bainite, which has a large TS fluctuation with respect to the holding temperature, is suppressed, and as a result, the YR is stabilized, a predetermined YR can be obtained, and a steel sheet with better material stability can be obtained. In order to fully obtain such effects, it is preferable that the ratio of the C content in the fresh martensite to the C content in the steel sheet is 1.50 or more. More preferably, it is 1.60 or more. Although there is no particular upper limit set for the ratio of the amount of C contained in fresh martensite to the amount of C contained in the steel sheet, it is preferably 7.00 or less, and more preferably 6.50 or less.

[0048] (3) Next, the manufacturing method and manufacturing conditions of the high strength steel plate (steel plate) will be described. [Hot rolling process] The heating conditions for the steel material are not particularly limited, but it is preferable to carry out the heating under the following conditions. Precipitates present at the heating stage of the steel material exist as coarse precipitates in the finally obtained steel sheet and do not contribute to strength, so it is preferable to re-melt the coarse precipitates precipitated during casting as much as possible. Furthermore, if they are not re-melted, the risk of trouble occurring during hot rolling due to an increase in rolling load increases. Furthermore, from the viewpoint of scaling off defects such as bubbles and segregation on the surface of the steel material, reducing cracks and unevenness on the steel sheet surface, and achieving a smooth steel sheet surface, it is preferable to heat the steel material to 1100°C or higher and 1.0 hour or more. On the other hand, there is no particular upper limit on the heating temperature of the steel material, but if the heating temperature of the steel material exceeds 1400°C, the scale loss increases with the increase in the amount of oxidation, and productivity decreases, so it is preferably 1400°C or lower. There is also no upper limit on the heating time, but it is preferable to set it to 48.0 hours or less from the viewpoint of suppressing decarburization from the slab surface layer due to heating.

[0049] Hot rolling finishing temperature: 800℃ or higher The steel material after heating is hot-rolled to become hot-rolled steel sheet. At this time, if the finishing rolling temperature is less than 800°C, the reduction ratio in the unrecrystallized state of austenite becomes high, abnormal texture develops, and the in-plane anisotropy in the final product becomes prominent. Furthermore, if the rolling is completed in the two-phase region, there will be some areas where C and Mn are significantly concentrated and some areas where they are not, depending on the phase. Since Mn has a slow diffusion speed, if such uneven distribution of Mn occurs, there will be some areas with high Mn concentration and some areas with low Mn concentration in the austenite produced by the heating and reheating processes. The areas with high Mn concentration exist as retained austenite, and the Mn concentration in the area that will eventually become tempered martensite will be low. As a result, it becomes difficult to obtain the specified YR, and the material stability will be impaired. In addition, the precipitates that were dissolved during heating of the steel material will be re-precipitated, which increases the rolling load, which increases the rolling load and hinders cold rolling. Therefore, the finish rolling delivery temperature in hot rolling, i.e., the finish rolling end temperature, is set to 800°C or higher, preferably 850°C or higher, and more preferably 870°C or higher. Although there is no particular upper limit for the finish rolling end temperature, if the finish rolling temperature exceeds 1000°C, the amount of oxide (scale) generated increases rapidly, the interface between the base steel and the oxide becomes rough, and the surface quality after pickling and cold rolling tends to deteriorate. In addition, the crystal grain size becomes excessively coarse, which may cause surface roughness of the pressed product during processing. Therefore, the temperature is preferably 950°C or less, more preferably 930°C or less, and even more preferably 900°C or less.

[0050] Coiling temperature after hot rolling: 700℃ or less If the coiling temperature after hot rolling is higher than 700°C, not only will the grain size of the hot-rolled sheet structure increase, but the area ratio of ferrite will also increase, and the area ratio of ferrite and bainitic ferrite will exceed 70% in the subsequent heat treatments of the heating and reheating processes, resulting in a strength of the final annealed sheet (final product) of less than 980 MPa. In addition, an oxide film that is difficult to remove by pickling will form on the surface of the hot-rolled sheet, which may cause a deterioration in the surface appearance after cold rolling. Therefore, the coiling temperature after hot rolling is set to 700°C or less. It is preferably 670°C or less. It is more preferably 650°C or less. Although there is no particular lower limit for the coiling temperature, if the temperature is lower than 350°C, the strength of the hot-rolled sheet increases, the rolling load in cold rolling increases, and defects in the sheet shape occur, resulting in reduced productivity. Therefore, the lower limit of the coiling temperature is preferably set to 350°C or higher, more preferably 370°C or higher, and even more preferably 400°C or higher.

[0051] The obtained hot-rolled steel sheet (hot-rolled coil) is subjected to hot-rolled sheet annealing in which the sheet is held at a temperature of Ac1 to Ac3 for 3 s to 216,000 s, which effectively promotes the concentration of Mn in martensite in the final structure. Therefore, this hot-rolled sheet annealing may be performed as necessary. Incidentally, Ac1 and Ac3 are defined by the following formulas. (Formula 7) Ac1=751-16.3[C]+34.9[Si]-27.5[Mn]-5.5[Cu]-15.9[Ni]+12.7[Cr]+3.4[Mo] (Formula 8) Ac3=881-205.7[C]+53.1[Si]-15[Mn]-20.1[Cu]-0.7[Cr]+41.1[Mo] Here, [C], [Si], [Mn], [Cu], [Ni], [Cr], and [Mo] in (Equation 7) and (Equation 8) each represent the mass percentage of the element contained in the steel.

[0052] Furthermore, the obtained hot-rolled steel sheet (hot-rolled coil) may be subjected to treatment such as pickling as necessary. The pickling method for the hot-rolled coil may be a conventional method. In addition, the hot-rolled coil may be subjected to skin pass rolling in order to correct the shape and improve the pickling property.

[0053] After hot rolling and / or pickling, the steel may be heat-treated as is, or may be cold-rolled and then heat-treated. When cold rolling is performed, the cold reduction is preferably 25% or more, and more preferably 30% or more. On the other hand, excessive reduction increases the rolling load and increases the load on the cold rolling mill, so the upper limit is preferably 75%, and more preferably 70% or less.

[0054] [Heating process] Heating temperature reached T0℃ As defined by formula 2, by setting the heating temperature T0°C to a temperature higher than the annealing temperature T1°C, it is possible to promote Mn concentration in martensite in the final structure. Therefore, the heating temperature T0°C is set to a temperature higher than the annealing temperature T1°C so as to satisfy the following formula 2. In addition, in order to cause austenite transformation in the heating process to make the fresh martensite fraction of the final structure 5% or more and the tempered martensite fraction 10% or more, the heating temperature T0°C needs to be Ac1 or more. In addition, although there is no particular upper limit set for the heating temperature T0°C, it is preferable that the heating temperature T0°C be Ac3 or less in consideration of the diffusion of Mn in two-phase annealing. (Formula 2)T1 <T0

[0055] Annealing temperature T1℃ The annealing temperature T1°C must satisfy formula 3 for the reasons described below. If the annealing temperature T1°C is 720°C or lower, the area ratio of ferrite generated during annealing becomes excessive, and the total area ratio of ferrite and bainitic ferrite exceeds 70%, resulting in a TS of less than 980MPa. On the other hand, if the annealing temperature T1°C is Ac3+100°C or higher, the total area ratio of ferrite and bainitic ferrite is less than 30%, resulting in poor ductility. Therefore, the annealing temperature T1°C must satisfy formula 3. (Formula 3)720 <T1<Ac3+100

[0056] Heating with heat input parameter Q between 3200 and 4800 The time t from Ac1°C during the heating process to the heating temperature T0°C through the heating end temperature T1°C h It is one of the important configuration items in the present invention that the heat input parameter Q (℃×min) defined by (Equation 4) using the annealing time t seconds at the annealing temperature T1℃ and the annealing temperature T1℃ is 3200 or more and 4800 or less.

[0057] The inventors conducted an experiment by varying the heat input parameter Q, and found that even at the same holding temperature, increasing the heat input parameter Q reduced the fresh martensite fraction and increased the tempered martensite fraction, and further changed the amount of Mn contained in the tempered martensite. In other words, as the heat input parameter Q increases, the fraction of austenite during annealing increases, decreasing the Mn concentration in austenite and increasing the fraction of martensite generated when cooling is stopped. The fresh martensite generated when cooling is stopped becomes tempered martensite by subsequent holding.

[0058] If the heat input parameter is less than 3200, the amount of Mn in the tempered martensite increases, i.e., the Mn concentration of the austenite during annealing increases. Therefore, although the bainite transformation is suppressed and the dimensional accuracy during forming increases, the amount of fresh martensite generated when cooling is stopped decreases, and reheating is performed with a large amount of untransformed austenite remaining. As a result, this untransformed austenite becomes fresh martensite during cooling after reheating, so the area ratio of fresh martensite in the final structure exceeds 35%, resulting in poor ductility. For this reason, the heat input parameter Q is set to 3200 or more. It is preferably 3250 or more, and more preferably 3300 or more. On the other hand, if the heat input parameter is more than 4800, the amount of Mn in the tempered martensite decreases, i.e., the ratio of the amount of Mn contained in the tempered martensite to the amount of Mn contained in the steel sheet becomes less than 1.05, and transformation to bainite with a large TS fluctuation with respect to the holding temperature in the reheating process is promoted, resulting in unstable YR and poor material stability. Therefore, the heat input parameter Q must be 4800 or less, preferably 3950 or less, and more preferably 3900 or less. (Formula 4)Q=[{(Ac1+T1) / 2}×t h / 60] + T1×t / 60

[0059] Cooling is performed under conditions where the average cooling rate from T1℃ to 400℃ is 5.0℃ / s or more. When the cooling start temperature is T1°C and the average cooling rate in the temperature range of T1°C to 400°C is less than 5.0°C / s, the transformation to bainite, which has a large TS fluctuation relative to the holding temperature, proceeds, resulting in a fluctuation in YR and impairing the material stability. Therefore, the average cooling rate in the temperature range of T1°C to 400°C is set to 5.0°C / s or more. There is no particular upper limit set for the cooling temperature in the temperature range of T1°C to 400°C, but in consideration of the cooling rate that can be industrially implemented, it is preferably set to 30.0°C / s or less. More preferably, it is set to 27.0°C / s or less.

[0060] [Reheating process] Cooling stop temperature Tsq℃: 150℃~370℃ In the annealing process, if cooling is stopped during cooling at a temperature lower than 150°C, the fresh martensite fraction generated at the time of cooling stop increases, the area ratio of tempered martensite exceeds 60.0%, the YR becomes excessively high, and the dimensional accuracy at the time of forming is poor. For this reason, the cooling stop temperature Tsq°C is set to 150°C or higher. On the other hand, if cooling is stopped at a temperature higher than 370°C, a large amount of austenite remains at the time of cooling stop, the area ratio of fresh martensite in the final structure becomes larger than 35%, the ductility decreases, the YR decreases, and the dimensional accuracy at the time of forming is poor. For this reason, the cooling stop temperature Tsq°C is set to 370°C or lower.

[0061] Holding temperature Toa℃: A temperature higher than the cooling stop temperature Tsq℃ and between 180℃ and 430℃ After cooling is stopped, by raising the temperature to a temperature higher than the cooling stop temperature, it is possible to turn the martensite generated when cooling was stopped into tempered martensite, and an excessive increase in YR can be suppressed. However, if the heating temperature is less than 180°C, the area ratio of tempered martensite is less than 10%, and TS is less than 980 MPa. On the other hand, if the heating temperature is more than 430°C, the area ratio of tempered martensite is more than 60%, and YR increases, resulting in poor dimensional accuracy during forming.

[0062] Hold at temperature Toa℃ for a period of time toa seconds. When the range of values ​​determined by Equation 5 based on the holding temperature and holding time in the reheating process satisfies a predetermined relationship with the heat input parameter Q defined by Equation 4 in the heating process, the C diffusion of fresh martensite during holding can be controlled and the steel sheet strength can be maintained.

[0063] If the value determined by formula 5 based on the holding temperature and holding time is less than Q / 10, the tempering due to holding will be insufficient, the area ratio of fresh martensite in the final structure will exceed 35%, and ductility will be poor. Therefore, the holding temperature Toa℃ and holding time toa seconds must satisfy formula 5. (Equation 5) Q / 10≦Toa(logtoa) On the other hand, if the value determined by the holding temperature and holding time exceeds Q / 5, C distribution from fresh martensite is promoted, and the ratio of the amount of C contained in fresh martensite to the amount of C contained in the steel sheet may become less than 1.50. In addition, C concentration in untransformed austenite remaining in the steel sheet is suppressed, so that transformation to bainite, which has a large TS variation relative to the holding temperature during holding, is promoted, and as a result, YR varies and material stability may be deteriorated. Therefore, it is preferable to satisfy formula 6. (Equation 6) Toa(logtoa)≦Q / 5

[0064] Plating When hot-dip galvanizing is performed, the steel sheet that has been subjected to the annealing treatment is immersed in a zinc plating bath at 440°C or higher and 500°C or lower to perform hot-dip galvanizing, and then the coating weight is adjusted by gas wiping or the like.

[0065] There are no special restrictions on the plating conditions, but the plating weight (amount per side) is set at 20 g / m from the standpoint of corrosion resistance and plating weight control. 2 From the viewpoint of adhesion, it is preferable that the thickness is 120 g / m or more. 2 The coating weight is preferably 25 g / m or less. 2 More preferably, it is 30 g / m or more. 2 It is even more preferable that the plating coverage is 100 g / m or more. 2 More preferably, it is 70 g / m or less. 2 It is even more preferred that:

[0066] For hot dip galvanizing, a galvanizing bath containing 0.08% to 0.30% Al is preferably used. Furthermore, the effects of the present invention are not affected even if the plating bath contains elements such as Pb, Sb, Fe, Mg, Mn, Ni, Ca, Ti, V, Cr, Co, and Sn in addition to Al, Mg, and Si.

[0067] When alloying treatment by hot dip galvanizing is performed, the alloying treatment by galvanizing is performed in a temperature range of 450°C or more and 600°C or less after the hot dip galvanizing treatment. If the alloying treatment is performed at a temperature exceeding 600°C, fresh martensite is transformed into tempered martensite, and the area ratio of fresh martensite becomes less than 5%, which may result in poor dimensional accuracy during forming. Therefore, when alloying treatment by galvanizing is performed, it is preferable to perform the alloying treatment by galvanizing in a temperature range of 450°C or more and 600°C or less. The Fe concentration of the plating layer of the alloyed hot dip galvanized steel sheet is preferably 8 to 17%. The alloying plating layer is formed by performing the alloying plating treatment.

[0068] The steel strip covered by the present invention also includes a coiled steel strip, and refers to a coil with a total length of 50 m to 3000 m.

[0069] (4) Materials Next, a member according to one embodiment of the present invention will be described.

[0070] A member according to an embodiment of the present invention is a member made of the high-strength steel plate according to the embodiment of the present invention described above. The member according to an embodiment of the present invention, for example, the member according to the embodiment of the present invention described above is preferably a member for a frame structural part of an automobile or a reinforcing part of an automobile.

[0071] Here, the high-strength steel sheet according to one embodiment of the present invention has a TS of 980 MPa or more, an El of 10% or more, and a YR of 50% to 85% and is excellent in material stability. Therefore, the member according to one embodiment of the present invention can contribute to reducing the weight of the vehicle body, and can be suitably used in general as a member for automobile frame structural parts or automobile reinforcing parts. EXAMPLES

[0072] Steel having the chemical composition shown in Table 1, with the balance being Fe and unavoidable impurities, was melted in a converter and made into slabs by continuous casting. The obtained slabs were hot rolled under the conditions shown in Table 2, then cold rolled, annealed, and reheated to obtain high-strength cold-rolled steel sheets (CR). Some of the steel was not cold rolled but was hot-rolled to obtain hot-rolled steel sheets (HR). Further, hot-dip galvanizing treatment was performed to obtain hot-dip galvanized steel sheets (GI) and galvannealed steel sheets (GA). For the hot-dip galvanizing bath, a zinc bath containing 0.19 mass% Al was used for the hot-dip galvanized steel sheets (GI), and a zinc bath containing 0.14 mass% Al was used for the galvannealed steel sheets (GA), with the bath temperature set to 465°C. The coating weight was 45 g / m per side. 2 (Double-sided plating) was used, and the Fe concentration in the plating layer of the GA was adjusted to be within the range of 9 mass % or more and 12 mass % or less. The cross-sectional microstructure, Mn and C contents in the microstructure, and tensile properties of the obtained steel sheets were investigated. The results are shown in Table 3.

[0073] [Table 1]

[0074] [Table 2]

[0075] [Table 3]

[0076] The area ratios of ferrite, bainitic ferrite, fresh martensite, and tempered martensite were determined by polishing a thickness cross section (L cross section) parallel to the rolling direction of the steel plate, etching it with nital, and observing 10 fields of view at 1 / 4 of the plate thickness position (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the steel plate surface) at 2000x magnification using a scanning electron microscope (SEM). The area ratios of each structure (total of ferrite and bainitic ferrite, tempered martensite, and fresh martensite) were calculated using the obtained structural images. In the above structural images, ferrite and bainitic ferrite were considered to be the black structural regions, fresh martensite was considered to be the light gray structural regions, and tempered martensite was considered to be the region where carbides precipitated in the dark gray structural regions.

[0077] The area fraction of retained austenite was determined by grinding the steel plate from the 1 / 4 position to 0.1 mm down, then chemically grinding a further 0.1 mm off the plate, measuring the integrated intensity ratios of the diffraction peaks of the {200}, {220}, and {311} planes of fcc iron and the {200}, {211}, and {220} planes of bcc iron using CoKα radiation in an X-ray diffractometer, and averaging the nine integrated intensity ratios obtained. When retained austenite was measured, the area fraction of retained austenite was subtracted from the area fraction of fresh martensite so that the total area fraction did not exceed 100%.

[0078] Furthermore, the area ratio of pearlite was determined by polishing a thickness cross section (L cross section) parallel to the rolling direction of the steel plate, etching it with nital, and observing 10 fields of view at 1 / 4 of the plate thickness position (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the steel plate surface) at 2000x magnification using a scanning electron microscope (SEM).The area ratio of pearlite was calculated by considering the area in which lamellar structure was confirmed in the obtained structure image as pearlite.

[0079] The tensile test was performed in accordance with JIS Z 2241 (2011) using a JIS No. 5 test piece, which was sampled so that the tensile direction was perpendicular to the rolling direction of the steel plate, and TS (tensile strength), YS (0.2% yield strength), and EL (total elongation) were measured. YR was calculated by dividing the YS value by TS. In the examples, steel plates with a TS of 980 MPa or more were judged to have passed the test because they achieved the target strength. Steel plates with an El of 10% or more were judged to have passed the test because they achieved the target formability. Steel plates with a YR of 50% to 85% were judged to have passed the test because they achieved the target dimensional accuracy.

[0080] The amount of Mn in the tempered martensite and the amount of C in the fresh martensite were measured by analysis with a FE-EPMA (field emission electron probe microanalyzer). The quantitative values ​​obtained were divided by the amounts of Mn and C contained in the steel sheet to determine the ratio of the amount of Mn in the tempered martensite to the amount of Mn in the steel sheet and the ratio of the amount of C in the fresh martensite to the amount of C in the steel sheet. The above EPMA measurements were performed in an 18μm x 18μm area at 1 / 4 of the plate thickness (a position equivalent to 1 / 4 of the plate thickness in the depth direction from the steel plate surface), with C analysis performed at an accelerating voltage of 7kV, current of 50nA, and analysis time of 20ms / pixel, and Mn analysis performed at an accelerating voltage of 9kV, current of 200nA, and analysis time of 100ms / pixel. C quantification was performed using a calibration curve using the XPP quantification results for a pure material and a steel sample with Si and Mn distribution.

[0081] The material stability was evaluated by preparing tensile test pieces at three locations, 1 / 4 width, 2 / 4 width, and 3 / 4 width, in the width direction of the steel plate described in the examples, and calculating the YR of these. If the variation in YR at the above three locations was 4% or less, it was judged as ◎, if it was more than 4% and less than 7%, it was judged as 〇, if it was more than 7% and less than 10%, it was judged as △, and if it was more than 10%, it was judged as ×. In the examples, the steel judged as × was used as a comparative example. When the evaluation object was a coil, the above evaluation was performed on the steel plate taken from the center of the coil. Furthermore, for the coil described in the examples, tensile test pieces were prepared at three locations, the front end, the center, and the tail end, of the entire length of the coil, as described below, and the YR of these test pieces was calculated. The material stability in the longitudinal direction of the coil was evaluated based on the variation in YR at the above three locations, and it was determined that a favorable material stability was obtained when the variation in YR was 10% or less, a more favorable material stability was obtained when the variation in YR was 7% or less, and an even more favorable material stability was obtained when the variation in YR was 4% or less. As for the method of taking samples from the entire length of the coil, the front end was taken at any location within the range from the front end to 1 / 10 of the entire length of the coil, the center was taken at any location within ±1 / 10 of the entire length of the coil in the longitudinal direction from the longitudinal 1 / 2 position of the entire length of the coil, and the tail end was taken at any location within the range from the tail end to 1 / 10 of the entire length of the coil. The above-mentioned sampling positions in the width direction were all 1 / 4 width.

[0082] The high-strength steel sheets of the examples of the present invention all have a steel sheet strength of 980 MPa or more, an El of 10% or more, and a YR of 50% to 85%, and are high-strength steel sheets with excellent mechanical stability. On the other hand, the comparative examples are inferior in at least one of the properties of strength and mechanical stability.

Claims

1. In mass percent, C: 0.020% or more and 0.200% or less, Si: 0.01% or more and 2.00% or less, Mn: 2.50% or more and 5.00% or less, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, N: 0.0100% or less; O: 0.0100% or less, C, Si, and Mn satisfy the following formula 1, The balance is composed of Fe and unavoidable impurities, The microstructure of the steel plate is The total area ratio of ferrite and bainitic ferrite is 30% or more and 70% or less, The area ratio of tempered martensite is 10% or more and 60% or less, The area ratio of fresh martensite is 5% or more and 35% or less, The remainder is at least one of retained austenite and pearlite, in terms of area ratio, of 0% or more and 20% or less, A high-strength steel plate, characterized in that the ratio of the amount of Mn contained in tempered martensite to the amount of Mn contained in the steel plate is 1.05 or more. However, the amount of Mn contained in the tempered martensite is expressed in mass %. (Formula 1) Mn / (C+Si)≧1.2 In formula 1, C, Si, and Mn each represent the mass percentage of each element.

2. Furthermore, the composition is as follows: Ti: 0.500% or less, Nb: 0.500% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 1.00% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, Bi: 0.200% or less, REM: 0.0100% or less, 2. The high strength steel plate according to claim 1, further comprising at least one or more elements selected from the group consisting of:

3. 2. The high strength steel plate according to claim 1, wherein a ratio of the amount of C contained in the fresh martensite to the amount of C contained in the steel plate is 1.50 or more. However, the amount of C contained in fresh martensite is expressed in mass %.

4. 3. The high strength steel plate according to claim 2, wherein a ratio of the amount of C contained in the fresh martensite to the amount of C contained in the steel plate is 1.50 or more. However, the amount of C contained in fresh martensite is expressed in mass %.

5. 5. The high strength steel sheet according to claim 1, further comprising a plating layer on the surface of the steel sheet.

6. The high strength steel plate according to claim 5, wherein the plating layer is an alloyed plating layer.

7. A steel strip comprising the high strength steel plate according to any one of claims 1 to 4.

8. A steel strip comprising the high strength steel plate according to claim 5.

9. A steel strip comprising the high strength steel plate according to claim 6.

10. A method for producing a high strength steel plate according to any one of claims 1 to 4, A hot rolling process in which a steel material having the composition according to claim 1 or 2 is heated, hot rolling is performed at a finish rolling end temperature of 800°C or more, and then coiling is performed at a coiling temperature of 700°C or less; After the hot rolling process, the heating temperature T 0 ° C., and then annealed to an annealing temperature T 1 Anneal at ℃, and start cooling at T 1 ° C., and T 1 a heating step of cooling the material at an average cooling rate of 5.0°C / s or more from 0°C to 400°C; Next, the cooling is performed to a cooling stop temperature Tsq ° C., which is 150 ° C. to 370 ° C., and the temperature is increased to a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and then the holding temperature Toa ° C. is a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and the holding time is toa seconds. In the heating process, the temperature is increased from Ac1° C. to the heating temperature T 0 ° C. through the annealing temperature T 1 Time to reach ° C. t h seconds and the annealing temperature T 1 Annealing time t seconds and annealing temperature T in ° C. 1 The heat input parameter Q defined by Equation 4 in terms of ° C. is 3200 or more and 4800 (° C. × min) or less, A method for producing a high strength steel plate, characterized in that in the reheating step, the holding temperature Toa °C, the holding time Toa seconds, and the heat input parameter Q satisfy Equation 5. (Formula 2) T 1 <T 0 (Formula 3) 720 < T 1 <Ac3+100 (Equation 4) Q = [ { (Ac1 + T 1 ) / 2} × t h / 60 ] + T 1 × t / 60 (Formula 5) Q / 10≦Toa(logtoa)

11. A method for producing a steel strip according to claim 7, comprising the steps of: A hot rolling process in which a steel material having the composition according to claim 1 or 2 is heated, hot rolling is performed at a finish rolling end temperature of 800°C or more, and then coiling is performed at a coiling temperature of 700°C or less; After the hot rolling process, the heating temperature T 0 ° C., and then annealed to an annealing temperature T 1 Anneal at ℃, and start cooling at T 1 ° C., and T 1 a heating step of cooling the material at an average cooling rate of 5.0°C / s or more from 0°C to 400°C; Next, the cooling is performed to a cooling stop temperature Tsq ° C., which is 150 ° C. to 370 ° C., and the temperature is increased to a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and then the holding temperature Toa ° C. is a temperature higher than the cooling stop temperature Tsq ° C. and 180 ° C. to 430 ° C., and the holding time is toa seconds. In the heating process, the temperature is increased from Ac1° C. to the heating temperature T 0 ° C. through the annealing temperature T 1 Time to reach ° C. t h seconds and the annealing temperature T 1 Annealing time t seconds and annealing temperature T in ° C. 1 The heat input parameter Q defined by Equation 4 in terms of ° C. is 3200 or more and 4800 (° C. × min) or less, A method for producing a steel strip, characterized in that in the reheating step, the holding temperature Toa °C, the holding time Toa seconds, and the heat input parameter Q satisfy Equation 5. (Formula 2) T 1 <T 0 (Formula 3) 720 < T 1 <Ac3+100 (Equation 4) Q = [ { (Ac1 + T 1 ) / 2} × t h / 60 ] + T 1 × t / 60 (Formula 5) Q / 10≦Toa(logtoa)

12. The method for producing a high strength steel plate according to claim 10, further comprising the step of cold rolling the steel plate after the hot rolling step and before the heating step.

13. The method for producing a high strength steel sheet according to claim 10, further comprising the step of: carrying out a plating treatment to form a plating layer on a surface of the steel sheet after the reheating step.

14. The method for producing a high strength steel sheet according to claim 12, further comprising the step of: carrying out a plating treatment to form a plating layer on a surface of the steel sheet after the reheating step.

15. A method for producing a steel strip according to claim 11, characterized in that after the hot rolling step and before the heating step, a cold rolling step is performed.

16. The method for producing a steel strip according to claim 11, further comprising the step of: carrying out a plating treatment to form a plating layer on the surface of the steel sheet after the reheating step.

17. The method for producing a steel strip according to claim 15, characterized in that after the reheating step, a plating treatment is carried out to form a plating layer on the surface of the steel sheet.

18. The method for producing a high strength steel sheet according to claim 13, wherein the plating treatment is an alloying plating treatment to form an alloying plating layer.

19. The method for producing a high strength steel plate according to claim 14, wherein the plating treatment is an alloying plating treatment to form an alloying plating layer.

20. The method for producing a steel strip according to claim 16, characterized in that the plating treatment is an alloying plating treatment to form an alloying plating layer.

21. The method for producing a steel strip according to claim 17, characterized in that the plating treatment is an alloying plating treatment to form an alloying plating layer.

22. A member, characterized in that it is made using the high strength steel plate according to any one of claims 1 to 4.

23. A member, comprising the high-strength steel plate according to claim 5.

24. A member, comprising the high-strength steel plate according to claim 6.

Citation Information

Patent Citations

  • Steel plates, components, and their manufacturing methods

    JP2022023087A

  • Container

    KR102368660B1

  • High-strength cold rolled steel sheet with low material non-uniformity and excellent formability, hot dipped galvanized steel sheet, and manufacturing method therefor

    US20180002771A1

  • High-strength steel sheet and production method therefor

    WO2016125463A1

  • High-strength cold-rolled steel sheet, high-strength plated steel sheet, and production methods therefor

    WO2019151017A1